Steroid-Resistant Extranodal Rosai-Dorfman Disease of Cheek Mass and Ptosis Treated with Radiation Therapy. (2nd May 2013) - Maklad, Ahmed Marzouk; Bayoumi, Yasser; Tunio, Mutahir; AlShakweer, Wafaa; Dahar, Mashooque A.; Akbar, Shomaila A.
Abstract : Background . Rosai-Dorfman Disease (RDD) is rare benign hematologic disorder of histiocytes, which usually manifests as painless lymphadenopathy, fever, leukocytosis and hypergammaglobulinemia. Extranodal RDD has been reported in 43% of cases, with skin as commonly involved site followed by head and neck region. However, soft tissue cheek mass is rare presentation of extra-nodal RDD. Case Presentation . A 26-year-old Saudi man presented with a six-month history of right cheek swelling and left upper eyelid swelling. Physical examination revealed right cheek mass of size 3 × 3 cm and left upper eyelid mass of size 1 × 2 cm and no palpable cervical lymphadenopathy. Incisional biopsy of cheek mass showed positivity for S100 and negativity for CD1a, consistent with extra-nodal RDD. Patient did not respond to systemic steroids and was given radiation therapy to left orbit with minimal response. Then, he was started on chemotherapy Rituximab, cyclophosphamide, vincristine, and prednisolone (RCVP) 8 cycles followed by reirradiation 10 Gy in 10 fractions with 6 MeV electron with complete response. After 12 months of followup, patient had recurrence in right cheek and was started on radiotherapy to the cheek mass. Conclusion . Extra-nodal RDD with involvement of cheek is a rare presentation. Incorporation of S100 and CD1a is helpful in diagnoses of RDD and differentiating it from other benign histiocytosis. Treatment consists of surgery, steroids, chemotherapy, and radiation therapy.